THE HISTORY OF THE FORMATION OF THE FUNDS OF THE STATE MUSEUM OF HISTORY OF UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article discusses the history of the formation of the funds of the State Museum of History of Uzbekistan, one of the largest museums in Uzbekistan today. It covers the existing collections from the time of the museum's establishment to the present day, as well as several collections that were active for a period but were modified or discontinued for various reasons.